Changes in Nutrient Accumulation and Transportation of Waxy Sorghum in Waxy Sorghum-Soybean Intercropping Systems Under Different Row Ratio Configurations - Wang, Can; Zhou, Lingbo; Gao, Jie; Zhang, Guobing; Peng, Fangli; Zhang, Chunlan; Zhao, Qiang; Peng, Qiu; Shao, Mingbo (Frontiers in Plant Science, 2022)
To determine the optimal row ratio configuration of waxy sorghum-soybean intercropping systems, a field experiment with seven treatments, including sole waxy sorghum (SW), sole soybean (SS), two rows of waxy sorghum alternated with one row of soybean (2W1S), two rows of waxy sorghum alternated with two rows of soybean (2W2S), three rows of waxy sorghum alternated with one row of soybean (3W1S), three rows of way sorghum alternated with two rows of soybean (3W2S), and three rows of way sorghum alternated with three rows of soybean (3W3S) was conducted during 2019 and 2020 in Guiyang, China. Accumulation and transportation of nitrogen (N), phosphorus (P), and potassium (K) in waxy sorghum were investigated. The results showed that the row ratio configurations had significant effects on the N, P, and K accumulation and transportation of waxy sorghum. On the one hand, compared to SW treatment, intercropping treatments showed higher N, P, and K contents and accumulation amounts, N, P, and K transportation amounts before anthesis, N, P, and K transportation rates before anthesis, and contribution rates of N, P, and K transportation before anthesis to grain of each organ in waxy sorghum. Similarly, the waxy sorghum-soybean intercropping system increased the yield components (including spike length, grain number per spike, and 1000-grain weight) of waxy sorghum. In addition, the yields of waxy sorghum and soybean among all treatments were in the sequence of SW (SS) > 2W1S > 3W1S > 3W2S > 3W3S > 2W2S. Besides, the 2W1S treatment showed the highest land equivalent ratio and economic benefit. On the whole, the waxy sorghum-soybean intercropping system can increase the N, P, and K absorption among organs and promote the N, P, and K transportation from vegetative organs to grain in waxy sorghum, so as to promote the growth and development of spike in waxy sorghum to obtain higher land equivalent ratio and economic benefit. The 2W1S treatment was recommended as the optimal row ratio configuration of waxy sorghum-soybean system to achieve the maximum utilization of nutrient resources.